Rice bran wax oleogel in an oil-in-water emulsion system - Zhang, Hui (2020)
In this thesis, the application of rice bran wax (RBW) oleogel into oil-in-water (o/w) emulsion systems was investigated in terms of the selection of an emulsifier to stabilise RBW emulsions, the morphology and thermal properties of RBW crystals, the influence of additives on properties of RBW crystals and emulsion droplets, as well as the in vitro lipid digestibility.